Effect of FGF-2 and PDGF-BB on a co-culture of human gingival fibroblasts and umbilical vein endothelial cells - Min Allah, Nasar Um; Zurairah Berahim; Azlina Ahmad; Kannan Thirumulu Ponnuraj (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gingival recession can be treated by root coverage procedure with tissue graft. The ideal gingiva graft should mimic the properties of the native gingiva. Gingival fibroblasts are main cells that reside in human gingiva, while the endothelial cells are the basis for blood vessel formation. The co-culture of these cells, will help in better understanding of gingival tissue regeneration. This study was aimed to determine the effects of fibroblast growth factor-2 (FGF-2) and plateletderived growth factor-BB (PDGF-BB) on a co-culture of human gingival fibroblasts (HGFs) and human umbilical vein endothelial cells (HUVECs). In this in vitro experimental study, the medium for the establishment of monolayer and coculture of these cells were first optimised. Then, the optimal concentrations of these growth factors were determined by assessing the cell viability using MTT assay. Next, to study the stimulatory effect of these growth factors, both HGF and HUVECs were co-cultured and gene expression analysis for fibroblast and angiogenic biomarkers was assessed using Real-Time RT-PCR. Cell viability assay showed that the effect of FGF-2 on HGF was dose-dependent and was optimum at a concentration of 5 ng mL-1, while that of PDGF-BB on HUVEC was optimum at a concentration of 20 ng mL-1. The stimulatory effect of FGF-2 and PDGF-BB was further supported by the Real-Time PCR results which showed that there is a significant expression of VIM, COL1A1, FN, CD31, VE-Cadherin, and vWF in the treatment group of both cells after three days of co-culture experiment, compared to control group. This study indicates a possible synergistic effect of FGF-2 and PDGF-BB growth factors in a co-culture of HGF and HUVEC leading to proangiogenic activity.